Fatal Paraquat Poisoning in a 15-Year-Old Girl (Journal of Enam Medical College, 2017)
Paraquat (dipyridylium) is a highly toxic compound with a pungent smell. It is commonly used for weed killing. Intoxication occurs mainly by oral ingestion. After ingestion severe impairment of multiple organs develops. There is no specific antidote. Treatment includes repeated activated charcoal hemoperfusion with pulse methylprednisolone, cyclophosphamide, and antioxidants. Here we report a case of 15-year-old girl who presented with history of attempted suicide with paraquat. Patient died due to respiratory failure despite aggressive treatment and hemodialysis.J Enam Med Col 2017; 7(2): 107-110